The Implementation Of The Story Presentation Method In Teaching Speaking Skills At The Arabic Language Development Center At The Dar Al-Najah Institute For The Academic Year 2021/2022: تنفيذ طريقة تقديم القصة في تعليم مهارة الكلام بمركز ترقية اللغة العربية في معهد دار النجاح لوماجانق للسنة الدراسية 2021/2022 م - Yusmi Muzayanah; Eni Zulfa Hidayah (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Speaking is the first productivity skill, and the main skill in language teaching. It is appropriate in the reality of teaching speaking skill at Darun Najah Lumajang Institute to prepare female students in the field of Arabic language skill as an attempt to prepare and print the young generation or female students capable of competing in a world that is reliable and of high quality in the field of Arabic language. In order to reach the best goal in teaching students' speaking skill, the teacher is confused about one of the existing theories, which is the way of presenting the story. The results obtained by the researcher from two previous questions are: The implementation of the method of presenting the story in teaching speaking skill, which are:1. Objectives, to provide students with the ability to study more knowledge of the language mentioned above, to train students to speak Arabic fluently, indicates the institution's vision and mission is to become a leading institution for the development of Arabic language.2. Material, Modern Conversational Book. 3. Method, presenting the story.4. Means: The Modern Dialogue Book, The Book of Al-Jarumiyeh, Al-Amrati, Al-Alfiya and Inflectional Examples, a blackboard.5. Steps: Introduction, basic activities, conclusion.6. Calendar: weekly calendar, formative or monthly calendar, summary calendar. Existing problems: the students do not hear the teacher’s voice, a non-resident teacher, The different backgrounds of the students’ studies in learning the Arabic language before him, the students’ lack of interest in education, and they were fed up with the teacher’s lack of innovation in techniques, strategies, and others. الكلام هو المهارة الأولى والأهم في تدريس اللغة. هذا هو الواقع في تعليم مهارات الكلام في معهد دار النجاح لوماجانج لإعداد الطالبات في مجال اللغة العربية كمحاولة لتصميم وطباعة جيل الشباب القادر على المنافسة في العالم الذي يتميز بالموثوقية والجودة العالية في مجال اللغة العربية. لتحقيق أفضل هدف في تعليم الطلاب مهارات الكلام، يحدد المعلم إحدى النظريات الموجودة، وهي تقديم القصص. النتائج التي حصل عليها الباحث من السؤالين السابقين هي تطبيق أساليب عرض القصة في تدريس مهارات الكلام ، وهي: 1. والهدف هو تزويد الطلاب، مع قدراتهم، وتعلم المزيد من المعرفة من اللغات المذكورة أعلاه، وتدريب الطلاب على الكلام باللغة العربية بطلاقة، وإظهار رؤية ورسالة المؤسسة هي أن تكون مؤسسة رائدة لتطوير اللغة العربية. 2. المواد، كتب المحادثة الحديثة. 3. الطريقة، تقديم القصة. 4. الوسائل: كتاب الحوار الحديث، كتاب الأجرومية، العمريطي، الألفية ابن مالك، ومثال الانعطاف، السبورة. 5. الخطوات: مقدمة، النشاط الرئيسي، الإختتام. 6. التقويم: التقويم الأسبوعي، التقويم التكويني أو الشهري، ملخص التقويم. المشاكل القائمة: لا يسمع الطلاب صوت المعلم، وخلفية مختلفة عن دراسات الطلاب في تعلم اللغة العربية من قبل، وعدم اهتمام الطلاب بالتعليم، وقد سئموا من افتقار المعلم إلى الابتكار في التقنيات والاستراتيجيات، وما إلى ذلك.